IMPROVEMENT OF D-DIMER, CRP, SGOT, AND SGPT IN COVID 19 PATIENTS WITH ADDITIONAL ORAL CYCLUS PROBIOTIC AND NASOPHARYNX SPRAY - Hans Otto Pratama Yohan; Eulis Alwi Datau; Juwita Soekarno; Eko E Surachmanto; Daniel Aditya; Muhammad Israd Badaru; Benny Theodore (Sean Institute, 2023)
Systemic infection of COVID-19 significantly impacts the hematopoietic system and hemostasis. Blood coagulation disorders are common in hospitalized COVID-19 patients. Elevated D-dimer levels have been consistently reported. Several studies have shown differences in the degree of elevation of liver test markers in COVID-19 patients, especially reporting levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and CRP. Aim of this study. To determine the efficacy of of oral cyclus probiotics, the combination of cyclus probiotics and propolis, honey, white turmeric, mint leaf extracts on patients in the COVID 19 isolation room with D-dimer, CRP, SGOT, and SGPT parameters. Monitoring was carried out only for up 7-10 days, although previously it was designed for 14 days, because of the policy to shorter the time of in patient treatment, this was related to moderate degree of Covid19 patients. Method. This study is a randomized control trial study with 26 samples as the manage group and 27 as the control group; was conducted at dr. R.D. Kandou General Hospital in December 2021-March 2022. Results. There was an improvement in D-dimer in COVID-19 patients in the manage group after administration of oral cyclus probiotics and nasopharyng spray of combination of cyclus probiotics, propolis, honey, white turmeric and mint leaf extracts, with a p value of 0.026. This probiotics studied had a significant effect on reducing D-dimer in Covid-19 patients. However, did not show a significant effect on CRP, SGOT and SGPT biomarkers. Maybe, the treatment time less than two weeks; as usually it will take two weeks to recover.